Molecular dynamic and pharmacological studies on protein‐engineered hirudin variants of Hirudinaria manillensis and Hirudo medicinalis. (15th March 2022) - Sun, Yan; Wang, Baochun; Pei, Jinli; Luo, Ying; Yuan, Nan; Xiao, Zhengpan; Wu, Hao; Luo, Chenghui; Wang, Jiaxuan; Wei, Shuangshuang; Pei, Yechun; Fu, Shengmiao; et al.
Abstract : Background and Purpose: Hirudin variants are the most powerful thrombin inhibitors discovered to date, with a lower risk of bleeding than heparin. For anticoagulation, the C‐termini of hirudin variants bind to the exocite I of thrombin. Anticoagulant effects of gene‐recombinant hirudin are weaker than natural hirudin for the reason of lacking tyrosine O ‐sulfation at C‐terminus. Experimental Approach: An integrative pharmacological study was carried out using molecular dynamic, molecular biological and in vivo and in vitro experiments to elucidate the anticoagulant effects of protein‐engineered hirudins. Key Results: Molecular dynamic analysis showed that modifications of the C‐termini of hirudin variant 1 of Hirudo medicinalis (HV1) and hirudin variant 2 of Hirudinaria manillensis (HM2) changed the binding energy of the C‐termini to human thrombin. The study indicated that Asp61 of HM2 that corresponds to sulfated Tyr63 of HV1 is critical for inhibiting thrombin activities. Further, the anticoagulant effects of HV1 and HM2 were improved when the amino acid residues adjacent to Asp61 were mutated to Asp. These improvements were prolongation of the activated partial thromboplastin time, prothrombin time and thrombin time of human blood, and decreased K i and IC50 values. In the in vivo experiments, mutations at C‐termini of HV1 and HM2 significantly changed partial thromboplastin time, prothrombin and thrombin time Conclusion and Implications: The study indicated that the anticoagulant effects of gene‐engineered HM2 are stronger than gene‐engineered HV1 and HM2‐E60D‐I62D has the strongest effects and could be an antithrombotic with better therapeutic effects.